2018
DOI: 10.1111/bpa.12643
|View full text |Cite
|
Sign up to set email alerts
|

Iron related changes in MS lesions and their validity to characterize MS lesion types and dynamics with Ultra‐high field magnetic resonance imaging

Abstract: Iron accumulates with age in the normal human brain. This process is altered at several levels in the brain of multiple sclerosis (MS) patients. Since iron is mainly stored in oligodendrocytes and myelin in the normal brain, its liberation in demyelinating lesions may amplify tissue damage in demyelinating lesions and its uptake in macrophages and microglia may help to more precisely define activity stages of the lesions. In addition, glia cells change their iron import, export and storage properties in MS les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 63 publications
1
34
0
1
Order By: Relevance
“…52 This should be taken into consideration when interpreting MWF results, especially in contexts such as aging or multiple sclerosis lesions, where changes in iron content are known to occur independently of myelin. [53][54][55] However, iron in WM is found mainly within oligodendrocytes, co-localized with myelin, 56 and intra-and inter-subject MWF variations are still believed to be driven primarily by myelin content.…”
Section: Comparison To Gold Standardmentioning
confidence: 99%
“…52 This should be taken into consideration when interpreting MWF results, especially in contexts such as aging or multiple sclerosis lesions, where changes in iron content are known to occur independently of myelin. [53][54][55] However, iron in WM is found mainly within oligodendrocytes, co-localized with myelin, 56 and intra-and inter-subject MWF variations are still believed to be driven primarily by myelin content.…”
Section: Comparison To Gold Standardmentioning
confidence: 99%
“…2c). Another study reported that iron was accumulated at the cortico-subcortical junction in the human brain [30]. We therefore performed Turnbull blue iron staining using coronal sections of the adult ferret brain and found an accumulation of iron in U-fiber regions ( Fig.…”
Section: Resultsmentioning
confidence: 90%
“…2f). Because iron is mainly stored in ferritin in myelin [30], it seems likely that the accumulation of iron in the U-fiber regions results from myelin accumulation in the U-fiber regions. These results suggest that iron accumulation is another feature of the U-fiber regions.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the use of MRI for microgliosis identification, less studies have tried to directly characterize microglial activation in specific brain regions. Changes of iron deposition, quantified using quantitative susceptibility mapping in MR, have been correlated with activated microglia/macrophages at edges of some chronic demyelinated lesions in patients suffering from multiple sclerosis (Dal-Bianco et al, 2017;Gillen et al, 2018;Hametner et al, 2018). Advanced diffusion models, based on neurite orientation dispersion and density imaging (NODDI) in MR, have been proved to be sensitive to microglial density and to the cellular changes associated with microglial activation in a preclinical setting (Yi et al, 2019).…”
Section: Pet and Mr Imaging Of Microglial Activationmentioning
confidence: 99%